2002
DOI: 10.1002/neu.10172
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomics of neural and behavioral plasticity

Abstract: How does the environment, particularly the social environment, influence brain and behavior and what are the underlying physiologic, molecular, and genetic mechanisms? Adaptations of brain and behavior to changes in the social or physical environment are common in the animal world, either as short-term (i.e., modulatory) or as long-term modifications (e.g., via gene expression changes) in behavioral or physiologic properties. The study of the mechanisms and constraints underlying these dynamic changes requires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
103
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(107 citation statements)
references
References 78 publications
1
103
0
3
Order By: Relevance
“…The general assumption was that only such genetic factors matter in an evolutionary context, as they can be transmitted through the germline to the next generation, and thereby cause transgenerational changes. However, the overwhelming bulk of recent research clearly demonstrates that most evolutionary changes, not least with respect to behaviour, appear to be associated with regulatory mutations (Andersson and Georges, 2004;Hofmann, 2003). These do not affect protein structure, but rather when and to what extent a particular protein is expressed.…”
Section: Epigenetics -Gene Expression and Regulatory Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The general assumption was that only such genetic factors matter in an evolutionary context, as they can be transmitted through the germline to the next generation, and thereby cause transgenerational changes. However, the overwhelming bulk of recent research clearly demonstrates that most evolutionary changes, not least with respect to behaviour, appear to be associated with regulatory mutations (Andersson and Georges, 2004;Hofmann, 2003). These do not affect protein structure, but rather when and to what extent a particular protein is expressed.…”
Section: Epigenetics -Gene Expression and Regulatory Mechanismsmentioning
confidence: 99%
“…It controls the timing and intensity of gene expression and therefore is crucial to understanding phenotypic differences between populations. As behavioural variation often correlates with variation in gene expression (Hofmann, 2003;Jöngren et al, 2010), epigenetic mechanisms should be important in behaviour regulation as well. However, the research area is still novel, and relatively unexplored.…”
Section: Epigenetic Mechanisms: What Causes Differences In Gene Exprementioning
confidence: 99%
“…It is well established that behavioural variation often correlates with variation in gene expression (Hofmann, 2003;Jöngren, Westander, Nätt, & Jensen, 2010), even if the mechanisms are so far not well understood. Therefore, epigenetic mechanisms should potentially be able to affect phenotypes such as behaviour by causing alterations in the expression of relevant genes or gene clusters (Jablonka, 2009).…”
Section: Epigenetics -Orchestration Of the Genomementioning
confidence: 99%
“…The contributions from psychosocial genomics have shown that socio-environmental experiences influence neurobiological structure and functions of brain across the life cycle (Garland & Howard, 2009). This is called 'Dynamic Gene Expression': the interplay between behavioural state-related gene expression (nature) and activity-dependent gene expression (nurture) bring about healing through neurogenesis and learning (Hofmann, 2003). Investigations of neuroplasticity demonstrate that the adult brain can continue to form novel neural connections and grow new neurons in response to learning or training even into old age.…”
Section: Dsm IV -Tr Cultural Formulationmentioning
confidence: 99%